2012
DOI: 10.1002/jaal.00057
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Literacy Classrooms Through Critical Dialogue

Abstract: Authors Fecho, Coombs, and McAuley discuss the integral role of dialogue in literacy classrooms dominated by standardized testing, curriculum, and instruction. Their argument in support of the dialogical literacy classroom begins with a historical and theoretical justification for these principles, then transitions into a discussion of the troubling condition of schools as a result of the current lack of dialogue. By including the voices of students and teachers, the authors offer glimpses into classrooms in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…This finding is in alignment with other research (Alvermann, 2009;Wilmot, Begoray, & Banister, 2013;Fecho, Coombs, & McAuley, 2012;Hare, 2012;Kanu, 2011) on the importance of collaboration for teenagers, and especially Indigenous youth, who value working and learning with and from others. In order for educators to be more inclusive generally, and culturally responsive specifically, it is important that learning is collaborative, authentic, and multimodal in order for students to express their understandings in meaningful ways.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in alignment with other research (Alvermann, 2009;Wilmot, Begoray, & Banister, 2013;Fecho, Coombs, & McAuley, 2012;Hare, 2012;Kanu, 2011) on the importance of collaboration for teenagers, and especially Indigenous youth, who value working and learning with and from others. In order for educators to be more inclusive generally, and culturally responsive specifically, it is important that learning is collaborative, authentic, and multimodal in order for students to express their understandings in meaningful ways.…”
Section: Discussionsupporting
confidence: 90%
“…Giving privilege to academic discourse has led to the segregation of large populations of students. Therefore, many researchers are now calling for a more dialogic approach to teaching, where multiple kinds of discourse are valued, discussion is collaborative, and the power of knowledge is shared between teacher and students, in order to help improve literacy and learning in the classroom (Alexander, 2008;Aukerman & Pandya, 2013;Fecho, Coombs & McAuley, 2012;Mercer & Howe, 2012).…”
Section: Dialogic Teaching and Exploratory Talkmentioning
confidence: 99%
“…Having students listen to, and reflect on, their own discussion will help bring them into formal argumentation discourse. Fecho et al(2012) have observed that many students do not see the potential of dialogical educational moments because of the monologic system they are used to. It is through dialogic learning and practices such as Socratic circles that teachers can highlight the value and importance of student Discourse.…”
Section: Educators Can Mediate Formal Argumentation Practices Throughmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque es posible que el alumnado pueda desarrollar individualmente y por escrito ciertas habilidades de lectura crítica, tiene un enorme interés la práctica de estrategias didácticas innovadoras asentadas sobre el diálogo crítico como método de trabajo (Chambers, 2007;Fecho;Coombs;McAuley, 2012), la cooperación y la interacción entre el alumnado y los coordinadores. Además, desde el punto de vista lingüístico-literario, una tertulia literaria dialógica permite acercar al alumnado a una actividad de ocio como la lectura que, en muchos casos, resulta novedosa.…”
Section: Discusión Y Conclusionesunclassified